Peroxisome Proliferator-Activated Receptor γ Regulates Lipid Metabolism in Sheep Trophoblast Cells through mTOR Pathway-Mediated Autophagy - Kexing Hao; Jing Wang; Hengbin Yu; Lei Chen; Weibin Zeng; Zhengrong Wang; Guangdong Hu (PPAR Research)
Peroxisome proliferator-activated receptor gamma (PPARγ) is a key nuclear receptor transcription factor that is highly expressed in trophoblastic cells during embryonic attachment and is accompanied by rapid cell proliferation and increased lipid accumulation. We previously showed that the autophagy pathway is activated in cells after activation of PPARγ, accompanied by increased lipid accumulation. In this study, we used PPARγ agonist rosiglitazone and inhibitor GW9662, as well as autophagy activator rapamycin and inhibitor 3-methyladenine, to unravel the probable mechanism of PPARγ engaged in lipid metabolism in sheep trophoblast cells (STCs). After 12 h, 24 h, and 48 h of drug treatment, the levels of autophagy-related proteins were detected by Western blot, the triglyceride content and MDA level of cells were detected by colorimetry, and the lipid droplets and lysosomes were localized by immunofluorescence. We found that PPARγ inhibited the activity of mammalian target of rapamycin (mTOR) pathway in STCs for a certain period of time, promoted the increase of autophagy and lysosome formation, and enhanced the accumulation of lipid droplets and triglycerides. Compared with cells whose PPARγ function is activated, blocking autophagy before activating PPARγ will hinder lipid accumulation in STCs. Pretreatment of cells with rapamycin promoted autophagy with results similar to rosiglitazone treatment, while inhibition of autophagy with 3-methyladenine reduced lysosome and lipid accumulation. Based on these observations, we conclude that PPARγ can induce autophagy by blocking the mTOR pathway, thereby promoting the accumulation of lipid droplets and lysosomal degradation, providing an energy basis for the rapid proliferation of trophoblast cells during embryo implantation. In brief, this study partially revealed the molecular regulatory mechanism of PPARγ, mTOR pathway, and autophagy on trophoblast cell lipid metabolism, which provides a theoretical basis for further exploring the functional regulatory network of trophoblast cells during the attachment of sheep embryos.